Evaluating the Teacher Professional Identity of Student Teachers: Development and Validation of the Teacher Professional Identity Scale - Wong, C.Y. Ethan; Liu, W. C. (Journal of Education, 2024)
This study sought to develop and validate an instrument to measure teacher professional identity of student teachers. Through a literature review, three indicators, namely teacher self-efficacy, commitment to teaching and professional orientation, were chosen to form the construct for validation. The factor structure was first tested through confirmatory factor analysis using a sample of 185 student teachers and cross-validated using a new sample of 412. Evidence from goodness-of-fit statistics, parameter estimates and internal consistency indicated that the three indicators are valid factors of the construct. The instrument can provide information to better meet the developmental needs of student teachers.
Keywords: Confirmatory Factor Analysis; Initial Teacher Education; Measurement Scale; Student Teachers; Teacher Professional Identity